2005
DOI: 10.1111/j.1439-0523.2005.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

SSR and SCAR markers linked to the fertility-restoring gene for a D2-type cytoplasmic male-sterile line in wheat

Abstract: ÔYi 4060Õ is an elite restorer line of a non-photoperiod-sensitive D 2 -type cytoplasmic male-sterile (CMS) line of wheat. Random amplified polymorphic DNA (RAPD) and simple sequence repeat (SSR) markers were employed to map one major fertility-restoring gene (D 2 Rf 1 ) in ÔYi 4060Õ. The sterile and fertile DNA pools were established from individuals in BC 6 , based on bulked segregant analysis. One RAPD marker E09, linked to D 2 Rf 1 , was converted to a SCAR marker and designated as E09-SCAR 865 . The genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…From the analysis of different sets of F 2 samples in 2 years, we identified the same major gene locus taf1 on chromosome 2DS associated with female fertility. This locus was different from any other locus associated with male fertility found in wheat so far (Ma, 1995 ;Fu, 2002 ;Liu, 2002;Xing, 2003;Zhang, 2003;Cao, 2004 ;Li, 2005 ;Guo, 2006). Based on our results, female fertility might be an independent genetic system different from that of male fertility.…”
Section: Discussioncontrasting
confidence: 90%
“…From the analysis of different sets of F 2 samples in 2 years, we identified the same major gene locus taf1 on chromosome 2DS associated with female fertility. This locus was different from any other locus associated with male fertility found in wheat so far (Ma, 1995 ;Fu, 2002 ;Liu, 2002;Xing, 2003;Zhang, 2003;Cao, 2004 ;Li, 2005 ;Guo, 2006). Based on our results, female fertility might be an independent genetic system different from that of male fertility.…”
Section: Discussioncontrasting
confidence: 90%
“…Despite some progress in CMS (Ahmed et al, 2001;Chen et al, 2009Chen et al, , 2010Liu et al, 2002Liu et al, , 2011, there is a dearth of information on the interceptive mechanism of CIMS (Adugna et al, 2004;Chakraborty and Devakumar, 2006;Parodi and Gaju, 2009;Rao et al, 2000). Despite some progress in CMS (Ahmed et al, 2001;Chen et al, 2009Chen et al, , 2010Liu et al, 2002Liu et al, , 2011, there is a dearth of information on the interceptive mechanism of CIMS (Adugna et al, 2004;Chakraborty and Devakumar, 2006;Parodi and Gaju, 2009;Rao et al, 2000).…”
mentioning
confidence: 99%
“…The mapping analysis indicated that the male sterile gene wptms3 located on chromosome 1B, flanked by Xgwm413 and Xgwm182, differed from those reported by Guo et al (2006b) and thus is a new gene. To date, several fertility restoring genes against CMS in wheat have been mapped on chromosome 1B (Ahmed et al, 2001;Li et al, 2005;Zhou et al, 2005). Therefore, there are regions on chromosome 1B related to fertility performance.…”
Section: Discussionmentioning
confidence: 99%